Islamic and International Legal Perspectives on Early Child Marriage: A Bibliometric Analysis - Ateng Ruhendi; Muhamad Kholid; Agus Mailana (Khazanah Hukum, 2026)
Early child marriage is a global issue with profound implications for children's health, education, and well-being, particularly among girls. This phenomenon remains a significant challenge in many countries, both in terms of response and academic understanding. This study aims to map the knowledge structure and research trends related to early child marriage using a bibliometric approach. The method combines quantitative and qualitative analyses, focusing on publications indexed in the Scopus database from 2013 to 2022. Data were collected using the keyword "early child marriage," resulting in 113 documents. After an initial screening of titles and abstracts, 111 articles were selected for further analysis. The indicators used include authors, articles, citations, institutions, and countries of origin. The findings show an increasing trend in publications in recent years, with specific institutions and countries dominating the scholarly contributions to this topic. This study contributes by providing a comprehensive overview of the development of early child marriage research and serving a foundation for future studies to identify research gaps and directions.